(untitled) (Journal of Science and Technology, 2016)
The objective of this paper is to describe the shortcomings of the standard technique for treatment of preauricular sinus (PAS) and to emphasize on an alternative modification of the standard surgical technique. PAS is a common congenital abnormality. Usually these lesions are asymptomatic. However, some patients complain of discharge and/or recurrent infections, requiring excision of the PAS. Surgical treatment of PAS is characterized by high recurrence rates. This paper describes our surgical experience in the treatment of PAS.